Effect of NPK Fertilizer and Burning Rice Husk Planting Media on the Growth of Spinach (Amaranthus tricolor L.) - Katrina, Katrina; Raksun, Ahmad; Mertha, I Gde (Jurnal Biologi Tropis, 2024)
Applying fertilizer can increase spinach productivity. Fertilization is necessary because the nutrients in the soil can be reduced as a result of being absorbed by plants continuously. For plants to thrive, there must be an adequate supply of nutrients. The purpose of this study is to ascertain the impact of roasted rice husk and NPK fertilizer, as well as the ideal ratio of the two to promote spinach development. A fully randomized design comprising two components, five treatment levels, and three replications was employed in this investigation. The plant height, number of leaves, leaf area, wet weight, and dry weight were all significantly impacted by the NPK fertilizer element, according to the Anova data. At 18 days after planting, the factor of burnt rice husk significantly affected plant height; however, at 35 days after planting, it had no significant influence. The interaction of NPK fertilizer and roasted rice husk had no significant effect on all observation parameters. The best treatment on plant height, leaf area, and wet weight was the dose of 200 g of roasted rice husk and 1.6 g NPK fertilizer, the best treatment on the number of leaves was the dose of 50 g of roasted rice husk and 1.6 g NPK fertilizer, the best treatment on dry weight was the dose of 100 g of roasted rice husk and 1.6 g NPK fertilizer.